The concept of gamification and statistical analysis of existing mobile applications on international business - Shyriaieva, N. V.; Rohozna, Valeriia; Adamkevych, Antoanella (Ужгородський національний університет, 2019)
The article considers the genesis of gamification and its implementation in the educational process. The essence of gamification experience, its role at the present time, and the perspectives of its adaptation for the students are discovered. The growing tendency of gamification popularization is analyzed based on data of Google Scholar. The authors suggest gamification as a tool to infuse ordinary activities with principles of engagement based on the gaming idea. The essence of applying of gamification in educational process for the motivation of students is proved. In the practical part of the research 100 existing mobile applications regarding the business activity and international business sphere are analyzed based on the data of Google Play. The founded applications and games are investigated by their availability according to prices, types, developers by countries and recommended age for users. The authors consider the frequency of functions of applications to reveal the most used types of mobile applications with the prospect of creation the most appropriate application for studying. The authors put forward some of applications for the detailed research to identify their specific features and aspects. At the final point the structure and content of an appropriate application according to the vision of authors are proposed.
Концепція гейміфікації та статистичний аналіз існуючих мобільних додатків з міжнародного бізнесу
Keywords: gamification; mobile business applications; business games; statistical analysis; education